How to manage catheter-related right atrial thrombosis: Our conservative approach. Issue 3 (May 2021) - Rossi, Luigi; Covella, Bianca; Libutti, Pasquale; Teutonico, Annalisa; Casucci, Francesco; Lomonte, Carlo
Background: Catheter-related right atrial thrombosis is an underestimated, severe, and life-threatening complication of any type of central venous catheters. No clear-cut epidemiological data are available. Catheter-related right atrial thrombosis is often asymptomatic; however, it can lead to serious complications and death. Case series: We report seven catheter-related right atrial thrombosis events occurred in five hemodialysis patients; two recurrences following primary treatment are included in the report, all of them managed with a conservative approach without catheter removal. Systemic anticoagulation (vitamin K antagonists), having a well-defined target of International Normalized Ratio of 2.5–3.0, combined with urokinase as a locking solution at the end of each hemodialysis session were the therapeutic strategy used in all patients. After the first month, the anticoagulation target was reduced to an International Normalized Ratio value of 1.5–2.0 and urokinase to a weekly administration. After sixth months, when no thrombus was identified at transthoracic echocardiographic examinations, the treatment was stopped. No bleeding complications were reported. Conclusion: The combination therapy here described is safe, quick, and effective, achieving the goal of not removing catheters.